Ccl3 enhances docetaxel chemosensitivity in breast cancer by triggering proinflammatory macrophage polarization. Issue 5 (25th May 2022) - Sheng, Dandan; Ma, Wei; Zhang, Rui; Zhou, Lei; Deng, Qiaodan; Tu, Juchuanli; Chen, Weilong; Zhang, Fuchuang; Gao, Nailong; Dong, Mengxue; Wang, Dong; Li, Fengkai; et al.
Abstract : Background: Although the antitumor efficacy of docetaxel (DTX) has long been attributed to the antimitotic activities, its impact on the tumor microenvironment (TME) has recently gained more attention. Macrophages are a major component of the TME and play a critical role in DTX efficacy; however, the underlying action mechanisms remain unclear. Methods: DTX chemotherapeutic efficacy was demonstrated via both macrophage depletion and C–C motif chemokine ligand 3 (Ccl3)-knockout transgenic allograft mouse model. Ccl3-knockdown and Ccl3-overexpressing breast cancer cell allografts were used for the in vivo study. Combination therapy was used to evaluate the effect of Ccl3 induction on DTX chemosensitivity. Vital regulatory molecules and pathways were identified using RNA sequencing. Macrophage phagocytosis of cancer cells and its influence on cancer cell proliferation under DTX treatment were assessed using an in vitro coculture assay. Serum and tumor samples from patients with breast cancer were used to demonstrate the clinical relevance of our study. Results: Our study revealed that Ccl3 induced by DTX in macrophages and cancer cells was indispensable for the chemotherapeutic efficacy of DTX. DTX-induced Ccl3 promoted proinflammatory macrophage polarization and subsequently facilitated phagocytosis of breast cancer cells and cancer stem cells. Ccl3 overexpression in cancer cells promoted proinflammatory macrophage polarization to suppress tumor progression and increase DTX chemosensitivity. Mechanistically, DTX induced Ccl3 by relieving the inhibition of cAMP-response element binding protein on Ccl3 via reactive oxygen species accumulation, and Ccl3 then promoted proinflammatory macrophage polarization via activation of the Ccl3–C-C motif chemokine receptor 5–p38/interferon regulatory factor 5 pathway. High CCL3 expression predicted better prognosis, and high CCL3 induction revealed better DTX chemosensitivity in patients with breast cancer. Furthermore, both the Creb inhibitor and recombinant mouse Ccl3 significantly enhanced DTX chemosensitivity. Conclusions: Our results indicate that Ccl3 induced by DTX triggers proinflammatory macrophage polarization and subsequently facilitates phagocytosis of cancer cells. Ccl3 induction in combination with DTX may provide a promising therapeutic rationale for increasing DTX chemosensitivity in breast cancer.